2012
DOI: 10.1002/art.33382
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases are dysregulated in rheumatoid arthritis and a novel histone deacetylase 3–selective inhibitor reduces interleukin‐6 production by peripheral blood mononuclear cells from rheumatoid arthritis patients

Abstract: Objective. To characterize the role of histone deacetylase (HDAC) activity in rheumatoid arthritis (RA) and to evaluate the effects of MI192, a novel HDAC-3-selective inhibitor, compared with the established nonselective HDAC inhibitor trichostatin A (TSA), on proinflammatory cytokine production.Methods. Activity of HDAC and histone acetyltransferase was measured in peripheral blood mononuclear cells (PBMCs) from RA patients by spectrophotometric assay, prior to and after 12 weeks of etanercept therapy. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 26 publications
0
102
0
Order By: Relevance
“…Different HDAC inhibitors (Table 1), which mostly target several members of HDAC, were described to have beneficial effects in vitro and in vivo in RA [17,[25][26][27][28][29][30][31]. However, many of the observed effects of HDAC inhibitors were shown to be chromatin-independent and nonepigenetic (reviewed in [17]).…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Different HDAC inhibitors (Table 1), which mostly target several members of HDAC, were described to have beneficial effects in vitro and in vivo in RA [17,[25][26][27][28][29][30][31]. However, many of the observed effects of HDAC inhibitors were shown to be chromatin-independent and nonepigenetic (reviewed in [17]).…”
Section: Histone Acetylationmentioning
confidence: 99%
“…The selective FPR2 antagonist WRW 4 was purchased from Calbiochem, Nottingham, UK. The PKC inhibitor (PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ) and the protein phosphatase 2 inhibitor (okadaic acid) were purchased from Tocris Bioscience, Bristol, UK.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Using the gene expression profile produced by the antiinflammatory pro-resolving molecule annexin A1 (AnxA1), 19 we found very strong positive connections with several members of the histone deacetylase inhibitors (HDACIs) class of drugs. HDACIs are being actively investigated for the treatment of cancer owing to their pro-apoptotic effect, 20,21 although a substantial body of evidence indicates that this chemically-unrelated family of molecules affords potent anti-inflammatory properties 22,23 with potential therapeutic in pathologies including rheumatoid arthritis, 24,25 inflammatory bowel disease 26 and heart disease. 27,28 The mechanisms underlying these anti-inflammatory properties of HDACIs are largely not understood.…”
mentioning
confidence: 99%
“…The fact that HDACi are a new class of drugs that might help combat the ongoing bone damage associated with RA, has prompted a number of in vitro and in vivo RA related studies [7,[21][22][23][99][100][101]. The first study to assess effects of HDACi using an animal model of inflammatory arthritis was reported in 2003 [85].…”
Section: Accepted Manuscriptmentioning
confidence: 99%